Phthiriasis Palpebrarum Case Treated with a New Medical Approach - Abdulhekim Yarbag; Hayrullah Yazar; Mehmet Köroğlu; Tayfur Demiray (Sakarya Tıp Dergisi)
Phthiriasis palpebrarum and is not a rare condition especially when hygienic conditions are inadequate. We present a case of phthiriasis palpebrarum in a 48-year-old female who was treated with a new medical approach, pure vaseline and povidone iodine mixture. Being more effective, cheaper, able to access it more easily and almost having no side effects are the advantages this regimen apart from others.